The Trinity and the New Testament - a Counter-Challenge to Dale Tuggy - Hasker, William 1935- (2021)
Dale Tuggy argues that my trinitarian views are in conflict with the theology of the New Testament; the New Testament, rather, is unitarian. I show several flaws in this argument, and point out the New Testament evidence that eventually led to the formulation of the doctrine of the Trinity.